The results of immunotherapy in patients with recurrent and metastatic human papilloma virus positive head and neck squamous cell carcinoma - A. V. Ignatova; Yu. V. Alymov (Опухоли головы и шеи, 2024)
Human papilloma virus (HPV), primarily type 16 (less commonly type 18), is associated with oropharyngeal squamous cell carcinoma (OPSCC). According to literature data, between 25 and 70 % of all cases of this cancer are linked to HPV infection. In the USA and some countries of the European Union, HPV-associated OPSCC comprises 60-70 % of all cases of head and neck squamous cell carcinoma. HPV-associated OPSCC is characterized by more favorable prognosis and higher survival compared to HPV-negative OPSCC. These types of this pathology are differently characterized in the 8th edition Tumor, Nodus and Metastasis (TNM). Significant differences in survival and disease prognosis led to studies aimed at deintensification of standard OPSCC treatment to minimize adverse events without the loss of effectiveness. Despite more favorable clinical progression, in 15 % of patients with HPV-associated OPSCC even after standard therapy recurrences and/or regional/distant metastases are observed which lead to unfavorable prognosis. Modern treatment schemes for recurrent/metastatic head and neck squamous cell carcinoma include immunotherapy, results of which also depend on HPV-status of the tumor. While clinical trials studying effectiveness of immune drugs include patients with HPV-positive tumors, data on treatment outcomes are contradictory, and molecular mechanisms of HPV effect on the immune response are not fully understood.The article summarizes the data on the effect of positive HPV status on the effectiveness of immunotherapy in patients with progressing/metastatic head and neck squamous cell carcinoma.